Taxonomy of species of Alicyclobacillus from South African orchards and fruit concentrate manufacturing environments and the prevention of fruit juice contamination - Groenewald, Willem Hermanus (Stellenbosch: University of Stellenbosch, 2009)
Thesis (PhD (Food Science))--University of Stellenbosch, 2009.